Estrogen Protects Vasomotor Functions in Rats During Catecholamine Stress - Zhang, Lin; Li, Chenfei; Yang, Liting; Adzika, Gabriel Komla; Machuki, Jeremiah Ong'achwa; Shi, Mingjin; Sun, Qi; Sun, Hong (Frontiers in Cardiovascular Medicine, 2021)
The incidence of dysfunctional vasomotor diseases has mostly occurred in postmenopausal women but not in premenopausal women. Hence, this study sought to investigate the impact of estrogen deficiency during catecholamine stress on vasomotor function. Also, attempts were made to utilize estrogen replacement therapy to mitigate the adverse effects (pathological remodeling) of stress on the aortic vessels to preserve vasomotor functions. To do this, female Sprague-Dawley (SD) rats were ovariectomized (OVX) along with sham operations (Sham). Day 15 after OVX operation, 17-estradiol (E2) was subcutaneously implanted (OVX+E2). Day 36 after operation, stress was induced by isoproterenol (ISO) subcutaneous injections. E2 prevented excessive weight gain in rats. Clinically relevant blood pressure indexes (systolic, diastolic, and mean atrial blood pressures) were assessed in the rats. Aortic vascular ring tensions were assessed in vitro to ascertain the impact of E2 on their vasomotor function. Aortic vascular rings (VRs) from OVX+ISO exhibited a significant increase in contractility in response to phenylephrine than VRs isolated from Sham+ISO rats. Also, sera levels of nitric oxide (NO) and endothelin-1 (ET-1) and the expression of p-eNOS/eNOS from vascular tissues were ascertained. We demonstrate that, during stress, OVX rats had higher blood pressures than those in the Sham group. Further, we showed that E2 decreases ET-1 expressions during stress while upregulating NO expressions via enhancing eNOS activities to facilitate vasomotor functions. Finally, histological assessment revealed the E2 treatments during stress preserved vasomotor functions by preventing excessive intima-media thickening and collagen depositions in the aortic vascular walls.